Solar Roof Distilling Tiles - Mohd Sharil, Muhammad Shameer (IRC, 2016)
Solar distillation is a great way to overcome water shortage and energy demand in this present day, where the energy from the sun is utilize to produce drinking water from seawater. A roof solar distilling tiles was developed with three different design to study the productivity based on the design. The study was focused on a scale study which means the experiment was conducted in one place which is in Universiti Teknologi Petronas, Sri Iskandar, Perak which the result may differ if conducting in other places where the weather is different. The solar roof distilling tiles were made as an enclosed chamber (0.3 x 0.25 m2); side and bottom are made of 2mm steel and the top side is covered with glass cover with inclination of 25o. A collector tray is installed at the end of the chamber to collect the condense water. Another two design were painted black with one of the basin will be occupied with aluminum fins